PSYCHOLOGİCAL PRİNCİPLES OF TEACHİNG FOREİGN LANGUAGE (Zamonaviy dunyoda pedagogika va psixologiya, 2022)
This article is based on the psychological principles of foreign language teaching. And containing the theories of scientists. The article explains that the psychological approach is more effective when teaching language to children. Opinions have been expressed on the theories of Clyne and Nariswariatmojo. The article explains how teachers should teach children on the basis of psychological principles and how many groups it should be divided into.